Comparative evaluation of sealing ability of two different biocompatible materials in repair of furcal perforation: An In vitro study - Rashu Grover (Dentistry and Medical Research, 2020)
Purpose: The purpose of this study was to evaluate the sealing ability and microleakage of Biodentine and mineral trioxide aggregate (MTA) Repair HP as furcal perforation repair materials. Materials and Methods: Twenty permanent mandibular molars were divided for ten samples each in Group I – Biodentine and Group II – MTA Repair HP. After access cavity preparation, artificial perforation was created and sealed with the repair material. Specimens were suspended in 2% methylene blue dye for 24 h and then split into longitudinal sections. After examining the depth of dye penetration under stereomicroscope, microleakage was calculated. Results: A higher mean microleakage was recorded in MTA Repair HP as compared to Biodentine. Conclusion: The study showed that Biodentine shows maximum sealing ability and least microleakage when compared with MTA Repair HP.